Melon oil methyl ester: an environmentally friendly fuel - Fasogbon, S. K. (JNRD - Journal of Natural Resources and Development, 2015)
Demand for energy is growing across the globe due to the direct relationship between the well-being and prosperity of people and energy usage. However, meeting this growing energy demand in a safe and environmentally friendly manner is a key challenge. To this end, methyl esters (biodiesels) have been and are being widely investigated as alternatives to fossil fuels in compression ignition engines. In this study, melon (Colocynthis Citrullus Lanatus) oil was used to synthesize biodiesel (methyl ester) using the transesterification method in the presence of a sodium hydroxide promoter. The emissions profile of the biodiesel was investigated by setting up a single-cylinder four-stroke air-cooled CI engine connected to a TD115-hydraulic dynamometer and an Eclipse Flue Gas Analyzer (FGA) with model number EGA4 flue gas analyzer. The engine was run at engine speeds of 675, 1200 and 1900rpm for biodiesel/diesel blends at 21°C on a volume basis of 0/100(B0), 10/90(B10), 20/80(B20), 30/70(B30), 40/60(B40) and 50/50(B50). The test showed a downward trend in the emissions profile of the biodiesel, with remarkable reductions of about 55% in the dangerous-carbon monoxide exhaust gas pollutant and 33.3% in the unfriendly SOX from 100% diesel to B30-biodiesel concentration. Increasing the speed from 675 to 1200 and then to 1900 rpm also afforded further reductions in CO and SOX exhaust emissions. NOX however increased marginally by 2.1% from the same 100% diesel to the B30-biodiesel composition. Based on the remarkable reduction in CO and SOX and the marginal increase in NOX as the concentration of the biodiesel increased in the blends, the study concludes that melon oil methyl ester is an environmentally friendly fuel.
Keywords: Melon Oil; Methyl ester; Environmental friendliness; Fuel; CO; SOX; NOX